An Investigation of Agreement between Clinical Educators and Peers in Rating Speech Pathology Students’ Interview Skills - Reece, Hannah; Hill, Anne E; Penman, Adriana (International Journal of Practice-based Learning in Health and Social Care, 2018)
Peer assessment and feedback is being used more frequently in health science education as it has been shown to enhance self-directed learning. This study investigated the level of agreement between clinical educators and speech pathology student peers when rating students’ performance during standardised patient interviews. Participating in this study were 104 undergraduate speech pathology students and six clinical educators who were required to rate students’ foundation clinical skills on the Standardised Patient Interview Rating Scale (SPIRS). Students’ skills, including communication, interviewing and professional practice, were rated by a clinical educator and a peer. Data from two separate interviews in weeks 4 and 8 of a clinical placement were analysed to determine the agreement between clinical educators and peers in rating a student on individual items on the SPIRS. Results indicated that there were unacceptable agreement levels between clinical educators and peers in both opportunities of rating. Recommendations for improving agreement between peers and clinical educators were made including increasing explicit training with the rating tool, increased collaboration between clinical educators and student raters, and using peers with more clinical placement experience as raters. Further research is required to investigate the use of peer assessment for both formative and summative purposes in speech pathology student education.